Construction of A Synthetic Gene Encoding the Multi-Epitope of Toxoplasma gondii and Demonstration of the Relevant Recombinant Protein Production: A Vaccine Candidate: - Karimi, Maryam; Seyyed Tabaei, Seyyed Javad; Ranjbar, Mohammad Mehdi; Fathi, Fardin; Jalili, Ali; Zamini, Ghasem; Javadi Mamaghani, Amirreza; Nazari, Javad; Roshani, Daem; Bagherani, Nooshin; Khademerfan, Mohammadbagher (Galen Medical Journal, 2020)
Background: Toxoplasma gondii is a widely-distributed parasite all over the world whose attributed severe afflicting complications in human necessitate the development of serodiagnostic tests and vaccines for it. Immunological responses to monovalent vaccines and the application of diagnostic reagents including single antigens are not optimally effective. Bioinformatics approaches were used to introduce these epitopes, predict their immunogenicity and preliminarily evaluate their potential as an effective DNA vaccine and for serodiagnostic goals. Materials and Methods: A 3D structure of proteins was predicted by I-TASSER server, and linear and conformational B cell and T cell epitopes were predicted using the online servers. Then, the predicted epitopes were constructed and called Toxoeb, and their expression in the prokaryotic and eukaryotic cells was demonstrated using SDS-PAGE. In the next step, Western blotting with pooled sera of mice infected with T. gondii was done. Results: The current in silico analysis revealed that the B cell epitopes with high immunogenicity for GRA4 protein were located in the residues 34-71, and 230-266, for GRA14 in 308-387, for SAG1 in 182-195, 261-278, and for GRA7 in residues 101-120, 160-176. The T cell epitopes were selected in overlapping regions with the B cell epitopes. The immunogenic region for GRA4 are in the residues 245-253, 50-58, and 40-54, for GRA14 in 307-315, 351-359, and 308-322, for SAG1 261-269, and 259-267, and for GRA7 in the residues 103-112, and 167-175. The results of the western blotting showed that the expressed protein had immunogenicity. Conclusion: Our constructed multi-epitope of T. gondii could be considered as a candidate for diagnostic and vaccination purposes. [GMJ.2020;9:e1708]